Neuropathic component of chronic musculoskeletal pain in patients with post-COVID-19: A cross-sectional study - Sevgi Gümüş Atalay,; Pınar Borman,; Ayşegül Yaman,; Evren Yaşar, (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate the neuropathic component of chronic musculoskeletal pain in post-coronavirus disease 2019 (COVID-19) and examine the relationship between neuropathic pain and clinical and demographic characteristics. Patients and methods: This cross-sectional study included 163 adult patients (85 females, 78 males; mean age: 41.7±4.3 years; range, 22 to 50 years) with post-COVID-19 musculoskeletal pain between February 1, 2021, and April 30, 2021. Demographic and clinical characteristics, including age, sex, affected site, duration, and severity of post-COVID-19 musculoskeletal pain using the Visual Analog Scale (VAS), as well as a neuropathic component of pain using the Leeds assessment of neuropathic symptoms and signs (LANSS), were collected. The most common post-COVID-19 symptoms, presence of hospitalization, and length of hospital stay during active COVID-19 infection were recorded from the patient records. Results: The mean duration and severity of pain were 7.85±1.53 months and 5.09±1.95, respectively. Half of the patients were hospitalized, and the mean length of hospital stay was 12.15±18.06 days. The most common pain sites were upper and lower back pain, followed by leg and arm pain. A total of 92 (56.4%) patients had previously received pharmacological or nonpharmacological treatment for post-COVID-19 musculoskeletal pain. Based on the LANSS (scores >12), 31 (19%) patients had neuropathic pain. There was a significant correlation between the presence of neuropathic pain and pulmonary involvement/symptoms. The presence and length of hospital stay were correlated with LANNS scores (p<0.05). The frequency, LANSS scores, and VAS-pain scores of the patients with and without neuropathic pain were similar between male and female patients (p>0.05). Conclusion: The neuropathic component of chronic musculoskeletal pain may be common, as one-fifth of our patients had neuropathic pain as assessed by the LANNS. Therefore, the awareness of post-COVID-19 chronic neuropathic musculoskeletal pain should be increased. We believe that focusing on the identification of pain phenotypes would provide adequate and tailored chronic neuropathic musculoskeletal pain management in the post-COVID-19 period.